Socializing the Impact: An Analysis of the Theory of Planned Behavior's Influence on Increasing University Students' Cybersecurity Awareness - Parikh, Varsha; Nimbekar, Mansi (Indonesian Journal Publisher, 2023)
The study aimed to assess cybersecurity awareness among university students in Vadodara, India, using the Theory of Planned Behavior (TPB) framework. The study involved 242 students from selected universities, selected using a snowball sampling method. Data was collected through Google Forms and email, and the Statistical Package for the Social Sciences (SPSS) programme was used for statistical analysis. The majority of students were young (18-23 years old), with moderate internet usage and primary digital competency skills. Only 17% reported experiencing issues during cyber surfing. The study found that most students had low awareness, lower knowledge, and negative perceptions about cybersecurity. Most students followed unsafe cybersecurity practices and had a negative attitude towards cybersecurity. The study also examined the correlation between TPB constructs.